Characterization and optimization of bioactive compounds from herbal plants using microwave assisted infusion - Mohd Shafie, Nor Shafawati (2020)
Phytochemicals study of herbal plants have received increased attention due to the biological benefits to human health, especially on oxidative stress related disease. Recently, microwave oven is favourable in extracting herbal plant phytochemicals due to the effectiveness in extracting the bioactive compounds. In this study, optimization of microwave assisted infusion (MAI) parameters based on selected herbal plants activities from conventional infusion was carried out. The parameters investigated were microwave power, brewing time and irradiation time. In conventional infusion, phytochemical content, antioxidant and antiacetylcholinesterase activities of six herbal plants of Andrographis paniculata, Clinacanthus nutans, Morinda citrifolia, Piper sarmentosum, Strobilanthes crispus and Vernonia amygdalina were evaluated. P. sarmentosum infusion showed antiacetylcholinesterase activity of 39.66% that was the highest among six medicinal plants. P. sarmentosum infusion also showed highest total phenolic content (TPC) and ferric reducing antioxidant power (FRAP) reducing activity at 245.64 mg GAE/L and 359.95 mg Fe2+/L, respectively. A. paniculata infusion showed total flavonoid content (TFC) of 41.71 mg RE/L, whereas S. crispus infusion showed highest 2,2’-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) antioxidant activity with 59.92 mg AEAC/L. While C. nutans infusion showed 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition activity of 64.09%. P. sarmentosum was chosen in MAI as this plant showed good activities in TPC, FRAP and AChE assay. The optimal conditions were 560 W, 495 sec of brewing time and 240 sec of irradiation time. Under optimal condition, the maximum recovery were TPC (141.48 ± 3.78 mg GAE/L), TFC (31.62 ± 0.45 mg RE/L), FRAP (327.7 ± 8.20 mg Fe2+/L), DPPH and AChE inhibition (30.87 ± 0.27 %; 45.65 ± 0.69 %). From gas chromatography mass spectrometry (GC-MS) and Fourier transform infrared (FTIR) results, chemical compound of diethyl phthalate was identified in the MAI of P sarmentosum formulation. The finding of this study can be considered as the baseline study in exploring the use of microwave to aid in plant infusion preparation.